THE EFFECT OF DELAYS DUE TO FLIGHT OPERATION HANDLING AND ENGINEERING ON ON-TIME PERFORMANCE AT PT. WATER LAMPS AT SOEKARNO HATTA AIRPORT - Amelia Trisavinaningdiah; Asriani Susiati; Ria Puspitasari; Suci Alumdalu; Robah Lagu Sitepu (ZILLZELL MEDIA PRIMA, 2025)
The purpose of this study is to determine the effect of delays that occur in the handling of flight operations on on-time performance, the effect of delays that occur in technical handling on on-time performance and the effect of delays due to flight operations and techniques on on-time performance on airlines PT. Pelita Air at Soekarno Hatta Airport. In this study, researchers used a quantitative approach with SPSS ver. 27. A sample size of 50 respondents was obtained. Instrument regression tests were carried out, apart from that, statistical tests were also carried out, which included simple regression tests, multiple regression tests, simple correlation tests, multiple correlation tests, and determination of the coefficient of determination. Hypothesis testing was also carried out which included partial tests (t tests) and simultaneous tests (F tests). The results showed that Flight Operation had a significant positive effect on On-time Performance, Engineering had a significant positive effect on On-time Performance. The results of the F test show that the F-count value is 131.516 > 3.2 with Sig. 0.000 < 0.05. This means that the independent variables together have a significant effect on the dependent variable.